Flight of the Red Balloon - Hou Hsiao Hsien; Lee Ping Bing; Binoche, Juliette; Girardot, Hippolyte; Iteanu, Simon (Network, 2008)
A young boy has to deal with the increasing fragility of his mother, the loving yet preoccupied puppeteer Suzanne (Juliette Binoche). Overwhelmed by the demands of her chaotic existence, Suzanne hires a Taiwanese film student to help care for Simon. With him, a unique extended family is formed, utterly interdependent yet lost in their separate thoughts and dreams; all this is mirrored by a delicate, shiny red balloon that hovers above the Paris streets. [www.moviemail.com]